2018
DOI: 10.1155/2018/9132359
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sarcoma Lung Metastases with Stereotactic Body Radiotherapy

Abstract: Background The most common site of sarcoma metastasis is the lung. Surgical resection of pulmonary metastases and chemotherapy are treatment options that have been employed, but many patients are poor candidates for these treatments for multiple host or tumor-related reasons. In this group of patients, radiation might provide a less morbid treatment alternative. We sought to evaluate the efficacy of radiotherapy in the treatment of metastatic sarcoma to the lung. Methods Stereotactic body radiotherapy (SBRT) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 28 publications
1
43
1
Order By: Relevance
“…Rates of grade 2 pneumonitis were low in our series and these others, in which relatively few patients received multiple courses of lung SBRT, even though our series and the UCLA series had many patients previously treated with metastatectomy. These results are in contrast to the higher toxicity reported in the series by Lindsay et al 29 in which 44 patients were treated with SBRT to 117 separate sarcoma pulmonary metastases between 2005 and 2014. In that series, the median number of lesions treated per patient was 2 (range, 1‐7 lesions) and median lesion size was 2.1 cm (range, 0.8‐7 cm).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Rates of grade 2 pneumonitis were low in our series and these others, in which relatively few patients received multiple courses of lung SBRT, even though our series and the UCLA series had many patients previously treated with metastatectomy. These results are in contrast to the higher toxicity reported in the series by Lindsay et al 29 in which 44 patients were treated with SBRT to 117 separate sarcoma pulmonary metastases between 2005 and 2014. In that series, the median number of lesions treated per patient was 2 (range, 1‐7 lesions) and median lesion size was 2.1 cm (range, 0.8‐7 cm).…”
Section: Discussioncontrasting
confidence: 75%
“…Rates of pneumonitis in this series were higher (11 patients [25%] vs 1 patient [2%] in our series), which may be due to the higher percentage of patients receiving SBRT to more than one lesion, since the median lesion size (2.1 vs 2.0 cm) and radiation dose/fractionation were very similar between the two studies. Lindsay et al 29 reported one grade 3 complication (esophageal stricture requiring balloon dilatation).…”
Section: Discussionmentioning
confidence: 99%
“…This surprising finding suggests that further dose escalation beyond the standard fractionation currently used at our institution of 50 Gy in 5 fractions (BED 10 = 100 Gy) may be warranted for patients with OM‐HNSCC. Prior analyses using the same SABR dose‐fractionation and treatment strategy at our institution for patients with primarily T1‐2 non‐small cell lung cancer showed a 91% LC rate at 2 years and patients with lung metastases from soft tissue sarcoma had a 95% TM‐LC rate with a median follow‐up of 14.2 months, suggesting that this dose is sufficient for oligometastases of other primary sites . Alternatively, the findings may suggest that other local therapy options such as surgical metastasectomy may be considered in this patient population .…”
Section: Discussionmentioning
confidence: 89%
“…Definitive radiotherapy could be applied in selected patients with oligometastatic ES ( Figure 4 B–D). There is a growing number of evidence that stereotactic body radiotherapy (SBRT) is beneficial in patients with oligometastatic sarcomas, providing local control around 90% [ 89 , 90 ]. Palliative RT should be considered in the case of symptomatic ES metastases.…”
Section: Radiotherapymentioning
confidence: 99%